Integrating Blockchain Technology to Mitigate Trade Credit Risks and Boost SME Growth in Oman - Subramanian, Kabaly P; Al Qamashoui, Aziza Abdallah; V, Rengarajan; Jayashree, Rajendran; Christopher, B. Prabu; ., Ruksana (Journal of Ecohumanism, 2024)
In today’s worldwide economy, industrial expansion and technology drive national development. Globalization’s emphasis on entrepreneurship has spurred new graduates to start enterprises and boost economic growth. Due to Oman’s high unemployment rate, the government promotes SMEs to create jobs and enhance the economy. SMEs struggle to get capital, limiting their growth. They have trouble getting bank loans due to their size and lack of collateral. SMEs rely on trade financing due to its flexibility and cash flow relief. This study addresses SMEs’ trade credit management issues. It develops and implements a trade credit management plan to streamline credit operations, improve cash flow, eliminate bad debt, and improve financial health. This research also evaluates SMEs’ profitability, trade credit risks, and ways to reduce cash flow and financial stress. It also examines how Blockchain Technology can help SMEs. This research examines trade credit risks, returns, and costs and uses blockchain technology to propose solutions for SMEs and decision-makers. This research uses quantitative and qualitative analysis to survey SME businesses and bank officials in Oman’s South Al Batinah region about trade credit and Block chain technology usage. The experts suggested SMEs embrace Blockchain technology solutions matched to their size and business needs and hire an accountant for financial management.